IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK PENINGKATAN KEAKTIFAN PESERTA DIDIK DALAM MATA PEMBELAJARAN IPAS SISWA KELAS IV DI SD NEGERI 5 KAWAN BANGLI - I Dewa Ayu Diah Darmayanti; Nyoman Temon Astawa; Artana, Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in improving student learning activeness in the IPAS (Natural and Social Sciences) subject in Grade IV at SD Negeri 5 Kawan Bangli. The research employed a qualitative descriptive approach with a phenomenological design. Data were collected through participatory observation, in-depth interviews, and documentation. Informants consisted of the school principal, the Grade IV classroom teacher, and selected students. The findings reveal three main aspects: (1) the implementation of the PBL model was carried out systematically through the stages of problem presentation, group discussion, investigation, and presentation of results, thereby creating an active, interactive, and student-centered learning process; (2) several obstacles were encountered, including students lack of self-confidence in expressing opinions, differences in students learning abilities, and time constraints during discussions, which were addressed by the teacher through motivation, direct guidance, heterogeneous grouping, and effective time management; and (3) the application of the PBL model positively impacted students activeness, as evidenced by increased student participation, improved critical thinking skills, enhanced collaboration, and greater willingness to ask questions and respond during the learning process. These findings confirm that the Problem Based Learning model is effective in creating meaningful and active learning experiences in IPAS learning at the elementary school level. Keywords: Problem Based Learning, student activeness, IPAS, elementary school